2022
DOI: 10.1111/dom.14644
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of clinically important low glucose excursions with a long‐term implantable continuous glucose monitoring system in adults with type 1 diabetes prone to hypoglycaemia: the France Adoption Randomized Clinical Trial

Abstract: Aim: To assess the glucose control outcomes of the implantable Eversense real-time continuous glucose monitoring (CGM) system compared to self-monitoring of blood glucose or intermittently scanned CGM in patients with type 1 (T1D) or type 2 diabetes (T2D).Patients and Methods: This was a randomized (2:1), prospective, national, multicentre study. All participants, aged >18 years and on multiple daily insulin injections or insulin pump treatment, had a sensor inserted, which was activated only in the "enabled" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…However, a recently published randomised and prospective study [18] with the Eversense ® XL CGM System in nearly 150 patients with an HbA 1c of >8% compared the effect of the system between patients with implanted and activated sensors (enabled group) and implanted but inactivated sensors (control group). After 6 months, the HbA 1c was 0.1% lower in the enabled group, supporting our findings.…”
Section: Original Articlementioning
confidence: 99%
“…However, a recently published randomised and prospective study [18] with the Eversense ® XL CGM System in nearly 150 patients with an HbA 1c of >8% compared the effect of the system between patients with implanted and activated sensors (enabled group) and implanted but inactivated sensors (control group). After 6 months, the HbA 1c was 0.1% lower in the enabled group, supporting our findings.…”
Section: Original Articlementioning
confidence: 99%
“…In a larger population (N = 90 subjects) T1D subjects who spent greater than 1.5 h/day in hypoglycemia were given the Eversense © (Ascensia Diabetes Care, United States) CGM to determine if it decreased the time spent in hypoglycemia. Researchers found that after 3–4 months subjects decreased their TBR, which was associated with increased TIR and was sustained after 5–6 months ( Renard et al, 2022 ); however, hypoglycemia awareness status was not assessed in the trial. Decreased TBR could improve awareness; however, this study found ( Renard et al, 2022 ) no improvement in HbA1c after 6-month indicating that glycemic control was still not attained.…”
Section: Impaired Awareness Of Hypoglycemia (Iah) Therapiesmentioning
confidence: 99%
“…Researchers found that after 3–4 months subjects decreased their TBR, which was associated with increased TIR and was sustained after 5–6 months ( Renard et al, 2022 ); however, hypoglycemia awareness status was not assessed in the trial. Decreased TBR could improve awareness; however, this study found ( Renard et al, 2022 ) no improvement in HbA1c after 6-month indicating that glycemic control was still not attained.…”
Section: Impaired Awareness Of Hypoglycemia (Iah) Therapiesmentioning
confidence: 99%
“…Реальное клиническое использование системы Eversense в течение 180 дней было связано со значительным улучшением показателей HbA1c у взрослых с СД 1-го типа [42]. Рандомизированное клиническое исследование среди взрослых с СД 1-го типа, склонных к гипогликемии, во Франции показало, что система Eversense может значительно снизить TBR (<3 ммоль/л) у пациентов с СД 1, склонных к гипогликемии [43].…”
Section: непрерывный мониторинг глюкозыunclassified